Overloaded Adeno-Associated Virus as a Novel Gene Therapeutic Tool for Otoferlin-Related Deafness - Rankovic, Vladan; Vogl, Christian; Dörje, Nele M.; Bahader, Iman; Duque-Afonso, Carlos J.; Thirumalai, Anupriya; Weber, Thomas; Kusch, Kathrin; Strenzke, Nicola; Moser, Tobias (Frontiers in Molecular Neuroscience, 2021)
Hearing impairment is the most common sensory disorder in humans. So far, rehabilitation of profoundly deaf subjects relies on direct stimulation of the auditory nerve through cochlear implants. However, in some forms of genetic hearing impairment, the organ of Corti is structurally intact and therapeutic replacement of the mutated gene could potentially restore near natural hearing. In the case of defects of the otoferlin gene (OTOF), such gene therapy is hindered by the size of the coding sequence (~6 kb) exceeding the cargo capacity (<5 kb) of the preferred viral vector, adeno-associated virus (AAV). Recently, a dual-AAV approach was used to partially restore hearing in deaf otoferlin knock-out (Otof-KO) mice. Here, we employed in vitro and in vivo approaches to assess the gene-therapeutic potential of naturally-occurring and newly-developed synthetic AAVs overloaded with the full-length Otof coding sequence. Upon early postnatal injection into the cochlea of Otof-KO mice, overloaded AAVs drove specific expression of otoferlin in approximately 30% of all IHCs, as demonstrated by immunofluorescence labeling and polymerase chain reaction. Recordings of auditory brainstem responses and a behavioral assay demonstrated partial restoration of hearing. Together, our results suggest that viral gene therapy of DFNB9 – using a single overloaded AAV vector – is indeed feasible, reducing the complexity of gene transfer compared to dual-AAV approaches.